2013
DOI: 10.14219/jada.archive.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment intensity in frail older adults in the last year of life

Abstract: Background Palliative care focusing on pain and infection is recommended for patients who are terminally ill. It is difficult to implement this strategy in practice because of the lack of clear guidelines. The authors conducted a study to examine dental treatment provided to a group of long-term care (LTC) residents in the last year of life. Methods The authors retrospectively followed 197 LTC residents (60 years or older) in the last year of life to death. On the basis of the dental services patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
77
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 28 publications
2
77
0
2
Order By: Relevance
“…As a result of increased disease burden, physical and cognitive functional decline and psychological distress, the risk of dental caries and other oral disease can elevate in older adults at the end of life. These changes have been observed in NH residents who usually experience complex oral health decline as a result of progressive functional loss at the end of life 812 . However, how oral health changes over time in community-dwelling older adults at the end life is virtually unknown.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result of increased disease burden, physical and cognitive functional decline and psychological distress, the risk of dental caries and other oral disease can elevate in older adults at the end of life. These changes have been observed in NH residents who usually experience complex oral health decline as a result of progressive functional loss at the end of life 812 . However, how oral health changes over time in community-dwelling older adults at the end life is virtually unknown.…”
Section: Introductionmentioning
confidence: 98%
“…remain unstudied. The lack of information makes clinical treatment planning for end-of-life patients difficult and raises concerns for the quality of care for these vulnerable individuals 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that dementia, congestive heart failure and cancers were the most common medical condition found in the hospitalized older adults. 4 The cognitive dysfunction affects the capacity of individuals to complete daily activities, but also basic activities. The global cognitive dysfunction and inattention were the main features of acute confusional state (ACS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that 40% of remained teeth in patients with terminal illness were carious or retained roots. Almost 60% of patients who were hospitalized at the end of life did not receive any dental treatment before death 4 . It is sometimes difficult to perform the treatment, since there is a tendency of prolonged functional decline at this stage of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation